Bitcoin intraday time series momentum. Issue 2 (26th October 2021) - Shen, Dehua; Urquhart, Andrew; Wang, Pengfei
Abstract: This study examines intraday time series momentum in Bitcoin. Unlike stock markets, Bitcoin trades 24 h a day and therefore has not got a clear opening and closing period. Therefore, we use trading volume as a proxy for the market trading time and show that the first half‐hour positively predicts the last half‐hour return. We find that the first trading sessions with the highest volume or volatility are associated with the greatest predictability for intraday time series momentum. We also show that intraday momentum‐based trading yields substantial economic gains in terms of market timing and asset allocation, especially in periods of a market downturn in Bitcoin. Consistent with the finding in foreign exchange markets, our results also show that the Bitcoin intraday momentum is driven by liquidity provision rather than late‐informed trading.